Experimental and numerical analysis of a novel air-to-air heat recovery unit based on flat micro-heat pipe array technology for a laboratory animal house. (16th March 2022) - Wang, Mi; Fan, Hongming; Li, Jiatong
Abstract : All-fresh-air heating, ventilation, and air conditioning systems with high air exchange rates are typically applied in conventional laboratory animal houses (LAHs), resulting in high energy consumptions for fresh air handling. Therefore, exhaust air heat recovery (EAHR) systems are widely used for energy saving. In this study, a novel air-to-air heat recovery unit was proposed based on flat micro-heat pipe array technology and finned micro-heat pipe integration technique. This was used to recover waste heat from the exhaust air in a conventional LAH in Beijing. The heat recovery performance was experimentally and numerically investigated. The results show that the maximum heat recovery capacity, heat recovery efficiency, and of performance are 39.0 kW, 83.6%, and 17.8, respectively, in winter, and are 21.1 kW, 81.6%, and 9.6, respectively, in the transition season. The heat recovery capacity and efficiency decrease from 44.3 to 3.3 kW and from 83.4% to 63.0%, respectively, when fresh air temperature increases from −7 to 22 °C. When the air velocity increases from 1.0 to 3.0 m/s, the reduction of the heat recovery efficiency is approximately 4%, and the pressure loss increases from 36.9 to 159.6 Pa. Overall, the EAHR unit shows better performance than traditional units.